Self‐reported rates of interpersonal conflict vary as a function of questionnaire format: Why age‐related trends in disagreement (and other events) may not be what they seem. Issue 7 (1st August 2014) - Dirghangi, Shrija; Laursen, Brett; Puder, Justin; Bjorklund, David F.; DeLay, Dawn
ABSTRACT: Two studies examine whether self‐reports of interpersonal conflict differ as a function of how the question is asked. In Study 1, 56 U.S. college students ( M  = 20.7 years) completed different versions of a questionnaire, four times, at one week intervals. Participants reported more conflicts with the aid of memory prompts than without, an effect that was especially strong when questions focused on events from the previous day. In Study 2, 123 middle‐school students ( M  = 11.08 years) and 128 primary school students ( M  = 8.2 years) from the same region completed one of two questionnaires describing conflict during the previous day. Children reported more conflicts with memory prompts than without. The effect was twice as strong for younger children than older children. The findings suggest that increases in reports of conflict across the transition into adolescence may be due to improvements in the ability to recall and recount events in the absence of memory cues.